Harmonising regulatory information on wine protected designation of origin in Europe - Sebastian Candiago; Simon Tscholl; Leonardo Bassani; Helder Fraga; Lukas Egarter Vigl (IVES Technical Reviews, 2022)
Wine Protected Designation of Origin (PDO) products are strictly regulated and therefore highly susceptible to changes in climatic, environmental and socioeconomic conditions. Analysing the impacts of such changes has so far been challenging, because the legal specifications of wine PDOs in Europe have never been summarised in a harmonised dataset. Here, we present how we created the first inventory of regulatory information for the 1177 wine PDO in Europe, based on the geographical indication register of the European Union.